A new species in Hieracium sect. Alpina (Asteraceae) from the Western Carpathians in Slovakia - Chrtek, Jindřich; Szeląg, Zbigniew (Phytotaxa, 2026)
Hieracium scituliforme is a new, tetraploid (x=9) apomictic species from the subalpine zone in the Nízke Tatry Mts., Slovakia. It combines morphological features of the H. fritzei agg. and probably H. stygium and/or H. nigrescens agg., and belongs to the H. scitulum aggregate.